The Relationship between Online Learning and Student Satisfaction with Training Quality in Private Universities during the COVID-19 Pandemic - Nhan, Pham Nguyen Trong; Lan, Nguyen Mai; Hien, Ta Huu; Phuong, Nguyen Thi Thuy; Phi, Nguyen Tran Ngoc (Journal of Education and e-Learning Research, 2022)
This study aims to explore the relationship between the influential factors of online learning and the satisfaction of economics and business majors with the quality of their training in the context of the Covid-19 pandemic. A total of 900 students in private universities completed a questionnaire. The principal findings of this research are that the students are satisfied with their online learning and that learning conferencing software is the most important driving factor leading to the students’ satisfaction when compared with learning conditions and learning devices. Another interesting finding is that the experience of using learning conferencing software results in a slight difference in the students’ perceived level of satisfaction, adding that users with more than two years’ experience are more satisfied with their training quality than users with less than one year’s experience. However, the results also show that students want to switch to offline learning when the pandemic is over. This study should, therefore, be of value to higher education authorities wishing to understand their students’ perceptions of online learning. In addition, results from the study suggest more managerial approaches as well as improve the online teaching quality during the pandemic.